Geotechnical characterization of the clay soils of Pucallpa - Hernández Aguilar, Marco Antonio (2023)
This article addresses in detail the geotechnical characterization of fine soils in the city of Pucallpa, in the Amazon region of Peru. With the main objective of describing the mechanical behavior and the very particular physical characteristics of these fine clay-type soils in the areas of Yarinacocha, Manantay and Callería, for this purpose, a geotechnical campaign was carried out that consisted of the execution of 40 manual excavations of the open-air pit type with depths of up to 1.50 meters, with the purpose of recovering unaltered samples in the form of cubes of 0.40 m on each side, for subsequent transfer to the soil mechanics laboratory of the Ricardo Palma University, where they were They carried out normal and special tests to obtain their physical and mechanical characteristics. The samples are characterized by the predominance of fine clay-type particles of high and low plasticity with SUCS classification of CL, CH, with moisture content values ​​of up to 30%, reddish, gray and in some cases brown in color, the liquid limit content exceeds 35% in most samples and with a plasticity index that averages 20%, in addition, unit or volumetric weight tests, specific weight tests of the solids were carried out to determine their specific gravity Gs, tests granulometry by sedimentation, one-dimensional consolidation test and simple compression tests on unaltered and remoulded samples, data that have allowed us to know, understand and comprehend the behavior of the fine clay soils of the city of Pucallpa in its three main districts, being able to obtain their main physical properties, resistance and deformation allowing zoning and characterizing the clay soils of the city of Pucallpa.